Level of Knowledge among Medical Student Regarding The Role of Vitamin C For Skin Health in Universitas Sumatera Utara - Nova Zairina Lubis; Hening Yumi Wardoyo Putri (Talenta Publisher, 2022)
BACKGROUND: The main function of vitamin C for skin health is as an antioxidant, combating environmental oxidative stress, which helps the natural regeneration of environmental oxidative stressors, collagen formation and brightening the skin. Humans cannot synthesize their own vitamin C, so to meet the vitamin C needs of the body, humans must consume vitamin C from fresh fruits and vegetables. In addition to oral and topical use, the practice of using vitamin C by injection has also been widely spread in major cities in Indonesia. Taking vitamin C is not something bad, but using vitamin C that is not according to the recommended dosage can have unwanted effects on health. OBJECTIVE: This study aims to determine the level of knowledge of students at the Faculty of Medicine, Universitas Sumatera Utara to regarding the role of vitamin C for skin health in 2020. METHODS: This study used a descriptive observational method with a cross sectional design. The sample size in this study was 247 people. The samples used were students of Faculty of Medicine at the Universitas Sumatera Utara class 2017, 2018, and 2019. Data on student knowledge levels collected from the results of filling out the questionnaire will be grouped using the Guttman scale and forwarded for further data processing using the Statistical Package for Social Sciences (SPSS) program 25 . RESULTS : In this study it was found that 86.3% of respondents had sufficient knowledge about the role of vitamin C for skin health, 91.2% of female respondents had sufficient knowledge, 81.5% of male respondents had sufficient knowledge. Based on how to use vitamin C, it can be seen that 41.9% of students have high knowledge about the use of vitamin C orally, 60% of respondents have sufficient knowledge about the use of vitamin C topically, and 50.4% of respondents have sufficient knowledge about its use vitamin C by injection. CONCLUSION: The level of knowledge of students at the Faculty of Medicine at the Universitas Sumatera Utara, for 2017, 2018 and 2019 regarding the role of vitamin C for skin health is sufficient. There are differences in the level of knowledge according to gender in this study, it was found that women have a better level of knowledge than men.